Management of a Septic Open Abdomen Patient with Spontaneous Jejunal Perforation after Emergent C/S with Confounding Factor of Mild Acute Pancreatitis - Fahri Yetisir; Akgün Ebru Sarer; Hasan Zafer Acar; Gokhan Osmanoglu; Mehmet Özer; Faik Yaylak (Case Reports in Surgery)
Introduction. We report the management of a septic Open Abdomen (OA) patient by the help of negative pressure therapy (NPT) and abdominal reapproximation anchor (ABRA) system in pregnant woman with spontaneous jejunal perforation after emergent cesarean section (C/S) with confounding factor of mild acute pancreatitis (AP). Presentation of Case. A 29-year-old and 34-week pregnant woman with AP underwent C/S. She was arrested after anesthesia induction and responded to cardiopulmonary resuscitation (CPR). There were only ash-colored serosanguinous fluid within abdomen during C/S. After C/S, she was transferred to intensive care unit (ICU) with vasopressor support. On postoperative 1st day, she underwent reoperation due to fecal fluid coming near the drainage. Leakage point could not be identified exactly and operation had to be deliberately abbreviated due to hemodynamic instability. NPT was applied. Two days later source control was provided by conversion of enteroatmospheric fistula (EAF) to jejunostomy. ABRA was added and OA was closed. No hernia developed at 10-month follow-up period. Conclusion. NPT application in septic OA patient may gain time to patient until adequate source control could be achieved. Using ABRA in conjunction with NPT increases the fascial closure rate in infected OA patient.